Investigation of the impact of the geometric dimensions of the impeller on the torque flow pump characteristics - Kondus, Vladyslav; Kotenko, Alexander (Eastern-European Journal of Enterprise Technologies, 2017)
Torque flow pumps (TFP) exhibit low indicators of energy efficiency. This is related to the features in the operating process of their flowing part. Given this, improvement of elements of the flowing part of TFP looks promising in terms of increasing their energy efficiency. Taking into account the structure of the pump life cycle cost, the most rational is the improvement of the impeller design without changing its overall dimensions. This will make it possible to increase the TFP efficiency with minimal investment cost. The study was conducted using the method of experiment planning. This allowed us to rapidly and accurately determine the extent of impact of the selected factors on the pump operating parameters. As a result of numerical investigation, we established the effect of the examined structural elements of the impeller on the pump parameters. A change in the design of the blade enabled a reduction of hydraulic losses in the inter-vane channels of the impeller. Alignment of the blade installation angle with the angle of a fluid inleakage decreased the resistance of input edge of the pump blade. As a result, hydraulic losses at the input of the impeller were reduced. The study conducted allowed us to improve efficiency of the torque flow pump by 4‒5 %. Adequacy of the results of numerical investigation was confirmed by performing a physical experiment.